2020
DOI: 10.18280/ijsdp.150413
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Ecological Welfare from the Recycling of Agricultural Resources and Its Influencing Factors

Abstract: This paper attempts to disclose how micro-subjects perceive the ecological welfare from the recycling of agricultural resources, and what are the factors affecting the perception. Firstly, the current status of modern agriculture was introduced, and the connotation of ecological welfare was explained in details. Then, the ecological welfare was divided into three aspects, namely, air quality change, water quality change, and farmland quality change. Meanwhile, eleven variables were selected, including seven pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Discussing the results of the study, one should compare them with similar ones in this area. A different group of scientists investigated [13][14][15] the main legal and social land relations. They came to the conclusion that such relations arise between public authorities at all levels and local governments, legal entities and citizens regarding the ownership of land and its use for its intended purpose, which, taking into account the special properties of land as an object of public relations, are mainly regulated land law and partly civil law to the extent that they are not regulated by land law.…”
Section: Discussionmentioning
confidence: 99%
“…Discussing the results of the study, one should compare them with similar ones in this area. A different group of scientists investigated [13][14][15] the main legal and social land relations. They came to the conclusion that such relations arise between public authorities at all levels and local governments, legal entities and citizens regarding the ownership of land and its use for its intended purpose, which, taking into account the special properties of land as an object of public relations, are mainly regulated land law and partly civil law to the extent that they are not regulated by land law.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Deng et al (2021) found that the spatial distribution pattern of EWP in China was the strongest in the eastern region and weak in the central and western regions. Third, in the study of influencing factors of EWP, some scholars have pointed out that economic contribution rate (Jorgenson and Dietz, 2015), industrial structure upgrading (Li et al, 2019), technological innovation (Cheng and wang, 2022), resource recycling (Geng, 2020), etc. all significantly impact on EWP.…”
Section: Research On Ecological Welfare Performancementioning
confidence: 99%
“…This initiative reflects a global trend where countries, albeit with different national conditions and approaches, generally support agricultural modernization through professional farmers' development. For example, in China, a highly developed country in the agricultural sector, there are agricultural colleges and experiment stations in every state, along with various agricultural education and training programs (Geng, 2020;Hu & Li, 2018). This has contributed to the formation of an extensive skilled labor force in the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on farmer training practices abroad have been ongoing for many years, resulting in a significant range of research findings. International academics have reached a consensus that to improve the economy of the agricultural sector and ensure the sustainability and quality of food production; it is imperative to develop farmers with high professional capabilities on a large enough scale (Geng, 2020;Randrianarison et al, 2017;Zeng et al, 2023). Research conducted by Zhang and his colleagues provides deep insights into the effect of training on farmers (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%